Determining focusing nozzle wear by measuring AWJ diameter - Prijatelj, Miha (Strojniški vestnik, 2017)
Abrasive water jet (AWJ) cutting is a versatile technology, but it is limited by relative poor accuracy. The main problem is the unknown diameter of the jet, as there is no device or instrument on the market that would enable a quick and easy measurement of it. With such an instrument the diameter could be regularly measured, nozzle wear monitored and noted offset adjusted. This would greatly improve the quality control of the process and the accuracy of the cut. This paper investigates the usage of a through-beam laser sensor for monitoring jet diameter and nozzle wear. Experiments were performed with five differently worn nozzles, with two different water pressures, with and without abrasive, at different standoff distances and with varying measuring times. Results show that the instrument is capable of monitoring the jet diameter and nozzle wear with an accuracy of +/-0.03 mm, but it is very susceptible to the jet's spray and abrasive sticking to the sensor's screens. Jet diameter correlated better with the diameter of the focusing nozzle when taking measurements without the abrasive, at high water pressures and at a standoff distance of 1 mm.
Keywords: abrazivni vodni curek; obraba šobe; premer curka; premer šobe